Effect of varying fibre loadings on the impact performance of kenaf and coir reinforced bioepoxy composites - Zainudin, M.Z.; Mansor, M.R.; Ali, M.B.; Jameel, Y.; Sapuan, S.M.; Basori (Persatuan Pembangunan & Industri Enau Malaysia, 2023)
This study describes the effect varying fibre loadings on the impact performance of kenaf and coir reinforced bioepoxy composites. A novel commercial type bioepoxy resin was applied to produce the composite, at fixed fibre loadings of 10, 20, 30, 40 and 50 wt%. Two types of bioepoxy composites were prepared, which are kenaf reinforced bioepoxy composites and coir reinforced bioepoxy composites, using untreated short fibre with average size between 3 mm to 5 mm. Hand layup process was applied to produce the composite samples, and later subjected to low velocity impact test according to ASTM D4812 standard. Results from the impact test showed that the highest impact energy and impact strength for kenaf reinforced bioepoxy composites and coir reinforced bioepoxy composites were obtained at 50 wt% fibre loadings. Comparison between both composites materials further revealed that coir reinforced bioepoxy composites showed higher impact energy and impact strength compared to kenaf reinforced bioepoxy composites for all fibre loadings (10 to 50 wt%). Furthermore, results obtained also showed that the neat bioepoxy has higher higher impact energy and impact strength compared to both kenaf and coir reinforced bioepoxy composites. This investigation has provided valuable insight on the application of bioepoxy in formulating green composites materials, and its effect to the impact mechanical property at varying fibre loadings.